Design and evaluation of a novel curved speed hump (CSH) for Indian roads - Korra Ravi Kiran; M. Kumar; Hazratullah Paktin (Transportation Research Interdisciplinary Perspectives)
Traffic calming measures are crucial for sustainable traffic management. Globally, vertical and horizontal techniques, such as speed humps, speed cushions, roundabouts and chicanes are used to reduce vehicle speeds and enhance road safety. While effective in achieving these goals, traditional traffic calming devices can have negative impacts on vehicles and the environment. To address these issues, a Curved Speed Hump (CSH) is introduced as a novel traffic calming solution specifically designed for Indian road conditions. CSH consists of a main speed hump, which is raised and curved structure positioned within a lane and complemented by an additional speed hump, adjacent to it. Motorists have the option to navigate along the curved trajectory, effectively moderating their speeds while mitigating the drawbacks typically associated with conventional vertical measures. This study outlines the CSHs objectives and geometric configuration. Through series of interconnected experimental field trials, including preliminary testing, driver perception studies, and real-world deployment. The final optimized design parameters obtained from the studies, features a radius of curvature (R) of the main CSH of 15 m, with lengths (L) of main CSH at 5 m and 6 m. Objective speed (Vb) for these parameters range from 20 km/h to 25 km/h and 30 km/h to 35 km/h, respectively. Driver perception studies for these parameters resulted in positive perceptions of comfort, safety, and speed reduction. Additionally, field implementation showed that the CSH outperformed traditional speed humps when comparisons were made to validate the CSH.